Assistive technology for speech disability patients via gesture recognition / Nor Adora Endut and Nurin Hazirah Mohd Zakir - Endut, Nor Adora; Mohd Zakir, Nurin Hazirah (Faculty of Computer and Mathematical Sciences, 2021)
Non-verbal communication via gesture recognition helps to minimize the problem faced by people with language or speech disability. Speech disability or disorder may be caused by weakened facial muscles because of neurological or other degenerative disorders. These impairments may either be temporary or permanent; but do cause difficulties in conveying the patients’ needs and thoughts to the people around them especially their caretakers. This project aims at developing assistive technology for speech disorder patients via gesture recognition using Internet of Things (IoT). Basic phrases in interpreted using a set of predefined gestures so that the patients may communicate their needs or a situation of emergency to the caretakers. Gesture sensors are used to detect the hand signals and notification is sent via mobile phones to alert the caretakers.